Economic decisions on the livestock production of highlanders to control zoonoses risk using Bayesian network analysis - Kallayanamitra, C. (Chiang Mai University, 2013)
Pig rearing continues to be an important source of food and serves for ritualuse among highlanders in Northern Thailand. The review of Trichinellosis outbreakreports from the past ten years (2003-2012) suggests that more than 90 percent of theoutbreaks have occurred in the highlands with several major foci scattered throughoutthe borderland provinces. To help us understand the transmission of the disease, theresearch applied an EcoHealth-One Health approach to develop a trandisciplinaryframework considering the interaction of highlanders with the pigs they grow andtheir environment as a single system. The research identified four subsystems toinvestigate Trichinellosis risk, including, animal husbandry, food chain, environment, and economic conditions. The research reported the results of a trandisciplinaryprocess involving the development of a Bayesian Belief Network model ofTrichinellosis risk and in-depth study of two highlander villages, including one thatexperienced an outbreak. The models provided a better understanding of thetransmission of Trichinella and solve the decision problems in management systemsrelated with pig production and public health concern to reduce Trichinellosis. Themodels and the survey results suggested that the above subsystems are entirelyinterdependent, and thus must be considered as an integrated whole when devisingdisease interventions.